Kogut w Biblii z uwzględnieniem jego narracyjnej funkcji pełnionej w Ewangeliach - Grochowski, Zbigniew Tadeusz (Verbum Vitae, 2017)
A once-wild jungle bird, Gallus gallus, was at some point domesticated, spread throughout the world, and became a universally popular source of meat and eggs (Section 1). The rich symbolism associated with this creature, drawn upon already by the authors of the Old Testament, issues from two characteristics of the male bird: its ability to distinguish between day and night (cf. Job 38:36; 3 Mac 5:23 LXX) and its caring and proud protectiveness toward the hens entrusted to him (cf. Prov 30:31 LXX) (Section 2). However, the cock is probably most famous for an event described in the New Testament: he figures in the episode within the Passion narrative where – according to the prophecy of Jesus (cf. Matt 26:34; Mc 14:30; Luc 22,34 and Jn 14:30) – the cock confirms by his crowing Peter’s threefold denial of Jesus (cf. Matt 26:69-75; Mc 14:66-72; Luc 22:54-62; Jn 18:15-27). It is worth noting that, while in the Synoptic Gospels the rooster becomes a recognizable sign (gnṓrisma) by which Peter is made aware of his error and is immediately aroused to profound grief (Section 3), in John’s Gospel the cock's crowing appears as an ironic and sad “last voice of the episode”, becoming for the reader a sign indicating that Jesus is the Prophet whose words are full of power. This gives rise to the hope that, just as the prior announcement of this dramatic event is fulfilled precisely, the prophecy regarding St. Peter’s martyrdom will likewise surely take place as spoken (cf. Jn 13:36; 21:18-19). Thanks to the future martyrdom of Peter, his fall will be fully redeemed, and the apostle, who will become the authentic disciple of Jesus, will be rehabilitated (Section 4).